THE INFLUENCE OF PREPARATORY STAGE IN CIVIL PROCEEDINGS ON HEARING A CASE WITHIN A REASONABLE TIME - Nekrošius, Vytautas; Simaitis, Rimantas; Vėbraitė, Vigita; Brazdeikis, Aurimas (Teisė, 2016)
This article analyses preparatory stage of civil proceedings and how it can influence the time period of hearing a case. The first section of the article distinguishes different models of preparatory stage. It is said that in Lithuania from year 2003 the main hearing model has been institutionalised but still some aspects of post-socialist model can be found. The second section examines the influence of different forms of preparatory stage on time period of hearing civil cases. The authors conclude that quite strict rules are set for preparatory stage in Lithuania and the court is not absolutely free to decide how it is the best to prepare the exact civil case for a court hearing. It is recommended to allow the courts to combine both oral and written forms of preparation in civil proceedings. The third section describe different other problems arising in preparatory stage in Lithuania. The authors stress that not legal regulation but sometimes inadequate understanding of the essence of preparatory stage by the court or participants to the proceedings causes the biggest problems in Lithuania. It has not been till the end conceived that during preparation it is the most important to formulate final claims and pleas of the parties to the dispute, also to submit all necessary evidence. Only in such way all the court hearings of civil disputes in courts of first instance will be smooth and without delays.